Numerical investigation of AC electric arc plasma heat dissipation in EAF. (16th March 2022) - Chen, Yuchao; Ryan, Steve; Silaen, Armin K.; Zhou, Chenn Q.
ABSTRACT: The alternating current (AC) electric arc furnace (EAF) is a crucial steelmaking facility consuming electricity to melt the recycled scrap. The arc heat dissipation impacts the scrap melting rate. The present study established a mathematical model to simulate the AC electric arc and estimate its heat dissipation under different arc operations. The study was aimed to deduce the relationship between arc operating current, arc length and the share of different arc heat dissipation mechanisms for future application in the scrap melting model. Validations of arc modelling were conducted by comparing the results against experimental data and simulations in the literature. A statistical method based on data sampling was proposed to determine the AC arc state variables to approximate the arc heat dissipation. A scrap melting experiment was designed and implemented in NLMK EAF to validate the amount of share determined in the present study for different arc heat dissipation mechanisms.